Zolpidem withdrawal seizure in an Iranian young woman: a case presentation - Pezhman Hadinezhad; Hamzeh Hosseini (Babol University of Medical Sciences, 2021)
Background: Zolpidem is a non-benzodiazepine drug, approved by FDA for sleep induction. Zolpidem is thought to be a safer drug than benzodiazepines (BZD) because of no evidence of abuse or dependence potential, but several case reports of zolpidem abuse and dependence have been published along with a small number of cases demonstrating seizures after sudden zolpidem withdrawal. Case presentation: A 32-year-old unmarried woman suffering from major depressive disorder had been taking zolpidem for insomnia for more than 1 year. She began to take zolpidem alone without mixing other kinds of hypnotics, and 50 mg of zolpidem used to be initially effective in treating her insomnia. In some days the dose increased up to 100 mg per day. In the end, she had to discontinue zolpidem abruptly because she could not afford it anymore. After 2 days, she suddenly showed facial spasm, mouth opening, tonic-clonic seizure, and loss of consciousness for about 1-2 minutes. Post-ictal confusion with clouded consciousness, psycho-motor retardation, persisted in 1 day. EEG in wakefulness revealed intermittent, generalized, diffused alpha wave and diffused sharp waves, and suggested seizure waves in the patient. Conclusion: Our case suggested that the potential of zolpidem dependence and withdrawal seizure are also present in the Iranian population. The female-gender, high dosage and long-term use of zolpidem might be risk factors for the development of adverse effects.